Iron-gall inks: a review of their degradation mechanisms and conservation treatments - Maria João Melo; Vanessa Otero; Paula Nabais; Natércia Teixeira; Fernando Pina; Conceição Casanova; Sara Fragoso; Sílvia O. Sequeira (Heritage Science, 2022)
Abstract Iron-gall inks are an essential element of our written cultural heritage that is at risk of a total loss due to degradation. This degradation leads to the loss of the support, particularly the cellulose-based support. Intending to stabilize it, we have come a long way from the nineteenth-century cellulose nitrate laminations to the relatively recent phytate treatments; nevertheless, less invasive treatments are needed. To pave the way for developing safer and more sustainable treatments, tailored as much as possible to the object, this paper reviews the conservation treatments and the advances that have taken place over the last decade in our understanding of the degradation mechanisms of iron-gall inks, based on a careful selection of references to support a concise microreview. This discussion is based on the currently accepted models based on the Fe3+-gallate and the identification of degradation products for iron-gall inks observed in heritage objects, including manuscripts dating from the fourteenth to seventeenth centuries and drawings from the fifteenth to nineteenth centuries. The degradation promoted by iron-gall inks induces scission of cellulose through acid catalysis and/or redox reactions. The causes of these acid-base and redox reactions are also assessed. Finally, we detail the state-of-the-art conservation treatments used to mitigate iron gall ink deterioration, covering treatments from the late nineteenth century to the beginning of the twentieth century, followed by the presentation of current phytate treatments and new postphytate treatments.